Low dose anti-thymocyte globulin reduces chronic graft-versus-host disease incidence rates after matched unrelated donor transplantation. Issue 7 (3rd July 2018) - Tandra, Anand; Covut, Fahrettin; Cooper, Brenda; Creger, Richard; Brister, Lauren; McQuigg, Bernadette; Caimi, Paolo; Malek, Ehsan; Tomlinson, Ben; Lazarus, Hillard M.; Otegbeye, Folashade; Kolk, Merle; et al.
Abstract: Anti-thymocyte globulin (ATG) is often added to hematopoietic stem cell transplant conditioning regimens to prevent graft rejection and reduce graft-versus-host disease (GVHD). Doses used in retrospective and prospective clinical trials have ranged from 2.5 to 20 mg/kg with rates of grade II–IV acute GVHD and chronic GVHD up to 40 and 60%, respectively. We retrospectively compared outcomes in recipients of matched unrelated donor (MUD) grafts given low dose rabbit ATG IV 3 mg/kg ( n  = 52) versus recipients of matched related donor (MRD) grafts ( n  = 48) without ATG. One year cumulative incidence of chronic GVHD was 25.2% in the MUD group versus 33.3% in the MRD group ( p  = .5). One-year cumulative incidence of extensive chronic GVHD was 9.6% in the MUD group versus 26.6% in the MRD group ( p  = .042). Our analysis supports the use of low dose ATG in MUD transplantation as an effective therapy to prevent chronic GVHD.